Potret Kekhalifahan Islam Dinamika Kepemimpinan Islam Pasca al-Khulafâ al-Râsyidûn hingga Turki Utsmani - Muhammad Khoirul Malik (Universitas Darussalam Gontor, 2017)
The change of Islamic government system was begun after the reign of al-Khulafâ’ al-Râsyidûn was completely over. The government system ruled by al-Khulafâ’ al-Râsyidûn democraticly was changed by the next successor of the reign to be monarchy. A caliph was not elected through democratic mechanism anymore, but was appointed by the previous caliph based on lineage. This era was very dynamic in Islamic political history. It was also having long moment and full of intrigues and polemics. The monarchy system ruled by the Umayyad Caliphate was also known by patrimonialism. It was the system of government which assigned a right to the caliph for claiming a state as his ownership and it could be inherited for his relatives, while his people were just considered as his subordinate who need his support and protection. According to this theory, the caliph authority was absolute and could not be interfered by others including constitutional law. The government system of the Abbasid Caliphate was not different from the Umayyad Caliphate. Both were rather similar, but the Abbasid Caliphate had some aspects as its identity. Another example of the government system could be found in Turkey. The Islamic government in there was represented by the Ottoman Empire for hundred years. The dynamics of Islamic politics is always influenced by some interactions of each regime or government, what makes a transition of power and politics so dynamic. Therefore, this article tries to describe how dynamic the governmet system of Islam in its history is.